AN ANALYSIS OF LINGUISTIC FORM, CHARACTERISTIC, AND FUNCTION OF SOBO LAWIKAN IN MERGOSONO - OKTANTO, ANGGA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Slang,  Sobo Lawikan,  Linguistic  forms,  Characteristics  and Function of slangThe main use of language is to communicate with each other. In society, there  are language varieties used by certain groups of community. One of  the varieties  is slang. People in Mergosono use the slang as one of the language varieties inside the community. This study aims to analyze the possible linguistic forms of the slang used by people in Mergosono and also to identify the characteristics and the functions of the slang.Qualitative  approach is used in this study. The source of the data are the result of observation and questionnaire. The data are utterances spoken by Mergosono people containing slang and the result of the questionnaire.This study reveals that the possible linguistic forms of the slang found  in  theMergosono are; syllable reversal, syllable reversal infix, infix, address term, and  coinage. Meanwhile, characteristics of Mergosono slang or Sobo Lawikan are  creative and fresh. The characteristics of flippant and onomatopoeic are not found  since there is no word adapted from the sound in nature,  and  also the Sobo Lawikan is the language of refinement which is used to show polite attitude. Further, is a language used to smoothen the delivered message which might not hurt addressee. In addition, it has been found that the function or the reason for the use of slang in Mergosono is because  people from Mergosono especially young adults want to  have  close  relationship  to  the community. It is done because they want  to  sustain  theirexistence  in  the community.The  result  of  the  study  is  expected  to  provide  some  useful  inputs which arevaluable for some students that are interested in Sociolinguistics. As for the next researcher who wishes to conduct a research on slangs, they can consider investigating the diffrences of slang in other place .